Efektifitas Media Flash Card Untuk Peningkatan Penguasaan Kalimat Bahasa Inggris - Edelbertus Witu (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study aims to determine how much the use of flash card learning media to improve students' mastery of English sentences. This research focuses on writing and speaking skills specifically to improve the mastery of English sentences so that students are able and confident to speak English well. This type of research is Classroom Action Research (CAR) which consists of four stages namely, planning, implementation, observation, and reflection. The research instruments used were observation sheets and test sheets. The subjects of the study were 39 grade XII Senior High School of St. Fransiskus Xaverius Boawae. The results of quantitative data indicate that the use of flash card learning media can improve students' mastery of English sentences in writing and speaking. This can be seen from the results of students' speaking ability has increased from cycle I to cycle II by 11%, from cycle II to cycle III by 29%. With flash card learning media make students more active and confident in speaking English. Flash card learning media are effectively used in the learning process.